Desempenho da Escrita de Palavras do português por aprendizes surdos: construção e avaliação de protocolo - Chaves, Adriana Di Donato (2013)
The present study describes the construction of the Evaluation of Deaf Students Word Writing Performance Protocol (PADEPAS - Protocolo de Avaliação do Desempenho da Escrita de Palavras por Aprendizes Surdos), and its steps of validation and reliability. Studies designed to validate an instrument of evaluation are developed through researches which establish reliability and relevance in measure procedures, focusing in specific aims. This protocol consists of a word nomination task by using the textual genre supermarket list with sociointeracionistic principals. It is inspired in studies of the psychogenesis of written language, based on the computational model and psychometric studies. As an instrument of second language for deaf people, o PADEPAS consider the learner s cultural characteristics in apprehending the world. It aims to contribute in evaluating the written learning process of deaf students in clinical and pedagogic approaches, suggesting levels of written performance for this population. The PADEPAS was elaborated for Brazilian Sign Language users who had finished Elementary School and present bilateral severe or profound hearing loss. The study was developed with 346 participants from Elementary School to University. From this total, 220 participants, aging from 9 to 55 years old, were selected to the studies of validation and reliability. The mean of years of education was 10,1 years. Half of the population was male and half was female, and they were all from the states of Pernambuco and Paraíba. Data was collected from March 2012 to December 2011. The PADEPAS had shown to be a consistent instrument with high level of reliability for the population studied, with 99,5% classified by the statistical test Cronbach, and 100% of context validation approval from deaf and hearing judges, obtaining results to digital and printed material patterns. After the conclusion of the validation steps with effect for this population, the PADEPAS can be suggested for validation and use in other states.